Effect on secondary care of providing enhanced support to residential and nursing home residents: a subgroup analysis of a retrospective matched cohort study. Issue 7 (7th April 2019) - Lloyd, Therese; Conti, Stefano; Santos, Filipe; Steventon, Adam
Abstract : Background: Thirteen residential care homes and 10 nursing homes specialising in older people in Rushcliffe, England, participated in an improvement programme. The enhanced support provided included regular visits from named general practitioners and additional training for care home staff. We assessed and compared the effect on hospital use for residents in residential and nursing homes, respectively. Methods: Using linked care home and administrative hospital data, we examined people aged 65 years or over who moved to a participating care home between 2014 and 2016 (n=568). We selected matched control residents who had similar characteristics to the residents receiving enhanced support and moved to similar care homes not participating in the enhanced support (n=568). Differences in hospital use were assessed for residents of each type of care home using multivariable regression. Results: Residents of participating residential care homes showed lower rates of potentially avoidable emergency admissions (rate ratio 0.50, 95% CI 0.30 to 0.82), emergency admissions (rate ratio 0.60, 95% CI 0.42 to 0.86) and Accident & Emergency attendances (0.57, 95% CI 0.40 to 0.81) than matched controls. Hospital bed days, outpatient attendances and the proportion of deaths that occurred out of hospital were not statistically different. For nursing home residents, there were no significant differences for any outcome. Conclusions: The enhanced support was associated with lower emergency hospital use for older people living in residential care homes but not for people living in nursing homes. This might be because there was more potential to reduce emergency care for people in residential care homes. In nursing homes, improvement programmes may need to be more tailored to residents' needs or the context of providing care in that setting.